The Power of a Diverse Mindset in Shaping Prosperity - Oded Galor; Marc Klemp; Daniel C. Wainstock (Center for Economic Studies and ifo Institute (CESifo), 2024)
Research spanning various disciplines underscores the significance of cultural diversity in facilitating cross-pollination of ideas, while diminishing social cohesiveness. Yet, the exploration of the impact of an equally intriguing dimension of diversity has remained uncharted: has the coalescence of diverse ancestral background in the formation of individuals' mindset shaped their productivity? Has a diverse mindset been central for individual's prosperity? This research advances the hypothesis that an intermediate level of diverse ancestral origins strikes a balance between the conflicting effects of cultural proximity and distinctiveness, creating an individual mindset that is conducive for productivity. While a limited cultural diversity among an individual's ancestors may reduce the scope for ancestral cross-pollination, and may diminish the individual's creativity, and adaptability, an extensive ancestral cultural divide could potentially hinder individual's coherence, human capital formation, and productivity. Leveraging the rich web of ancestries of the modern US population, we provide supporting evidence for the hypothesis and the underlying mechanism, establishing that there exists a hump-shaped relationship between intrapersonal diversity and earned income, mediated by the acquisition of human capital, in the form of educational attainment, originality, and flow of ideas.
Keywords: D60; O10; Z10; 330; mindset; diversity; culture; ancestry; productivity; human capital